Innovation of Lembang Vocational Training Center to Create Agricultural Entrepreneur - Setiawan, Timotius; Purnomo, Dwi; Ernah, Ernah (Agricore, 2018)
Lembang Vocational Training Center (Balai Latihan Kerja/BLK Lembang) is a government vocational training institution in charge of organizing vocational training in agriculture/agribusiness for the community, especially job seekers. The challenge faced by BLK Lembang is to create agricultural entrepreneurs expected to reduce 1.8 million unemployed in West Java (BPS, 2017). This study aims to investigate the innovations undertaken by BLK Lembang in creating agricultural entrepreneurs through agricultural vocational training. The study was conducted from November to December 2017 at BLK Lembang using qualitative descriptive method. Data were collected through secondary data, observation, in-depth interviews, and Focus Group Discussion (FGD) to several key informants. The results of this study showed that BLK Lembang has performed innovations in its vocational training system in order to create agricultural entrepreneurs that include: vision and planning, demonstration and training facilities, capacity building for instructor, training program development, training contents development, utilization of material practice, On Job Training Program, and networking. In the future, BLK Lembang will take opportunities for innovation in management and work culture, human resources, training programs, membership, facilities and partnership to improve its training system and quality in order to create more agricultural entrepreneurs.Keywords: agricultural entrepreneur, agricultural innovation system, agricultural vocational training